2010
DOI: 10.1007/s00701-010-0903-3
|View full text |Cite
|
Sign up to set email alerts
|

Use of twist-drill craniostomy with drain in evacuation of chronic subdural hematomas: independent predictors of recurrence

Abstract: TDC with drain has similar results in recurrence rates, morbidity, mortality, and outcome as other techniques as burr-hole craniostomy with drain. Preoperative and postoperative hematoma width and midline shift are independent predictors of recurrence. Brain re-expansion and time of drain maintenance are important factors related with recurrence of CSDH. Future CSDH reservoirs must avoid negative pressure and sudden pressure changes inside the whole closed drain system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…We found that the preoperative haematoma volume was a predictor of postoperative recurrence. Additionally, we found that the prognosis of no-recurrence was very high (94.4 %) in our cohort if the preoperative haematoma volume was under 115 ml, consistent with a general consideration that patients with large CSDH are at increased risk for the recurrence [10, 16, 24, 29]. Increased size of haematoma is attributed to brain atrophy associated with ageing, which may provide the CSDH with a potential space in which to grow [30].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We found that the preoperative haematoma volume was a predictor of postoperative recurrence. Additionally, we found that the prognosis of no-recurrence was very high (94.4 %) in our cohort if the preoperative haematoma volume was under 115 ml, consistent with a general consideration that patients with large CSDH are at increased risk for the recurrence [10, 16, 24, 29]. Increased size of haematoma is attributed to brain atrophy associated with ageing, which may provide the CSDH with a potential space in which to grow [30].…”
Section: Discussionsupporting
confidence: 86%
“…Numerous CT scan characteristics traditionally related to recurrence of CSDH have been reported and extensively discussed in the literature. These included bilateral site of CSDH [29], preoperative and postoperative haematoma width determined at the level of its maximum in-plane thickness [7, 8, 1014], preoperative and postoperative maximum midline displacement [2, 7, 8, 1012], haematoma densities [2, 4, 8, 13, 15–21], brain atrophy [19, 2224], intracranial extension [17], enhancement and thickness of inner membrane of CSDH [25, 26], postoperative presence of residual air accumulation in the CSDH cavity [4, 79, 19, 27] and postoperative persistence of residual CSDH space [4, 9, 12, 27]. However, the findings are not consistent between the studies.…”
Section: Introductionmentioning
confidence: 99%
“…[ 98 ] The results of TDC in terms of recurrence rates, morbidity, and mortality, are the same as compared to burr-hole craniostomy. [ 99 100 ]…”
Section: Twist Drill Craniostomymentioning
confidence: 99%
“…These included bilateral site of CSDH, preoperative and postoperative haematoma thickness or volume, preoperative and postoperative midline shift, haematoma densities, postoperative presence of air in the CSDH cavity, and postoperative persistence of residual CSDH space. [18,27,28] However, the influence of these CT features on outcome was not consistent between studies.…”
Section: Relationship Between Csdh's Rrr and Ct Characteristicsmentioning
confidence: 95%